A Key to Success: Building an Internal Trauma Education Program. Issue 4 (July 2016) - Pirrung, Joan Marie
Abstract : Developing an internal education program that specifically meets the needs of your trauma center's nurses is fundamentally an optimal method in educating. This article offers an overview of an internally developed trauma educational series that was created for novice and experienced nurses who work in a Level 1 trauma center.